Development of a Numerical Model for Vibration Analysis of Low Folded Shells under Dynamic Actions - Alé, A.A. Georges; Olodo, E. T. Emmanuel; DOKO, KOUANDETÉ VALERY; VIANOU, Antoine (My University, 2020)
In this work a numerical model is developed for vibration analysis of low folded shells under dynamic actions. At first it is done to describe the used finite element discrete model based on Lagrange variational principles. To solve the eigen value problem of these structures a numerical algorithm is proposed using Householder's QR-iteration transformations. This method provides a tridiagonal matrix whose eigen values coincide with those of the initial matrix and significantly reduces the iteration number compared to the Lanczos method. Implementation of the method is carried out on seven folded shell mathematical models. Obtained results show that accuracy can be improved and computational time can be significantly reduced compared to the methods available in the technical literature for this class of problems
Keywords: folded shells; numerical model; eigenvalues